Multistage Hiding Image Techniques - Nadia Mohammed (Al-Rafidain Journal of Computer Sciences and Mathematics)
In the few recent years computer sciences have been widely developed especially in communication spaces and Internet, therefore, a great need appear for security and safety of our information. Steganography is the science of hiding information or data (like a secret message) in other cover (like a digital image) in such a way that a normal person can't sense it. In this paper, four new methods were suggested in steganography systems to embed secret data in compressed images. Two methods are working in spatial domain, known as moving window and odd/even LSB, others are working in transform domain, known as odd/even DCT and DCT+DWT. The comparison results present that new methods are better than traditional methods in many characteristics, like (efficiency, security level, imperceptibility and robustness). The work was implemented using Matlab.